Analysis of salinity tolerance in two varieties of Medicago sativa at the vegetative stage. - Mounawer Badri; Khawla Rafik; Cheima Jabri; Ndiko Ludidi (Journal of Oasis Agriculture and Sustainable Development, 2021)
In this study, we analyzed salt tolerance in two varieties of Medicago sativa at the vegetative stage. Gabès2355 and Californian varieties of M. sativa were cultivated under control treatment and under a range of salt concentrations (50 mM, 100 mM, 150 mM, and 200 mM NaCl) in a greenhouse. At harvest, ten quantitative characters related to aerial and root growth were measured for plants of both varieties. Results from ANOVA showed that the variation of the traits measured is explained by the effects of variety, treatment and the interaction of variety x treatment. The treatment factor represents the most pronounced effect. While the Californian variety was more sensitive than the Gabès variety under 50 mM NaCl, it was the most tolerant under higher concentrations of NaCl. Specific correlations between measured traits were noted under control treatment and salt stress. Further work is needed to evaluate the agronomic performances of both varieties in the field under salinity constraint.